Formation of non-base-pairing DNA microgels using directed phase transition of amphiphilic monomers. Issue 7 (7th April 2022) - Lee, Chanseok; Do, Sungho; Lee, Jae Young; Kim, Minju; Kim, Sang Moon; Shin, Yongdae; Kim, Do-Nyun
Abstract: Programmability of DNA sequences enables the formation of synthetic DNA nanostructures and their macromolecular assemblies such as DNA hydrogels. The base pair-level interaction of DNA is a foundational and powerful mechanism to build DNA structures at the nanoscale; however, its temperature sensitivity and weak interaction force remain a barrier for the facile and scalable assembly of DNA structures toward higher-order structures. We conducted this study to provide an alternative, non-base-pairing approach to connect nanoscale DNA units to yield micrometer-sized gels based on the sequential phase transition of amphiphilic unit structures. Strong electrostatic interactions between DNA nanostructures and polyelectrolyte spermines led to the formation of giant phase-separated aggregates of monomer units. Gelation could be initiated by the addition of NaCl, which weakened the electrostatic DNA-spermine interaction while attractive interactions between cholesterols created stable networks by crosslinking DNA monomers. In contrast to the conventional DNA gelation techniques, our system used solid aggregates as a precursor for DNA microgels. Therefore, in situ gelation could be achieved by depositing aggregates on the desired substrate and subsequently initiating a phase transition. Our approach can expand the utility and functionality of DNA hydrogels by using more complex nucleic acid assemblies as unit structures and combining the technique with top-down microfabrication methods.